Avoiding antiperspirants during breast radiation therapy: Myth or sound advice?. Issue 2 (August 2017) - Baumann, Brian C.; Zeng, Chuan; Freedman, Gary M.; Verginadis, Ioannis I.; MacArthur, Kelly M.; Lin, Lilie L.; Vachani, Carolyn; Koumenis, Constantinos; Solberg, Timothy D.; Metz, James M.
Abstract: Breast cancer patients are typically advised to avoid antiperspirants for fear of increasing radiation dermatitis in the axilla. We hypothesized that antiperspirants would have minimal effect on skin dose. We found no difference in surface dose ± antiperspirants using 6 MV photons at gantry angles of 0°/30°/60°/90° regardless of aluminum concentration.